Osteocalcin As A Marker Of Bone Metabolism Disorders In Children With Juvenile Idiopathic Arthritis (Eurasian Medical Research Periodical, 2025)
To determine the relationship between osteocalcin and markers of inflammation and bone metabolism in children with juvenile idiopathic arthritis (JIA).